2019
DOI: 10.1029/2019gl082911
|View full text |Cite
|
Sign up to set email alerts
|

Rupture Process of the Mw 3.3 Earthquake in the St. Gallen 2013 Geothermal Reservoir, Switzerland

Abstract: We analyze slip distribution and rupture kinematics of a Mw3.3 induced event that occurred in the St. Gallen geothermal reservoir (NE Switzerland) in 2013. We carry out a two‐step procedure: (1) path effects are deconvolved from the seismograms using an empirical Green's function, resulting in relative source time functions at all seismic stations; (2) the relative source time functions are back‐projected to the corresponding isochrones on the fault plane. Results reveal that the mainshock rupture propagates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Here the direct problem is solved by computing slip at a set of control points (e.g., Emolo & Zollo, 2005) regularly distributed on the fault plane and then interpolating on a finer grid. To this aim we used a bilinear interpolation and filtered the slip map by using a Gaussian bi‐dimensional filter (e.g., Király‐Proag et al., 2019). The number of control points defines the size of the subfaults and is selected on the basis of the magnitude of the EGF.…”
Section: Methodsmentioning
confidence: 99%
“…Here the direct problem is solved by computing slip at a set of control points (e.g., Emolo & Zollo, 2005) regularly distributed on the fault plane and then interpolating on a finer grid. To this aim we used a bilinear interpolation and filtered the slip map by using a Gaussian bi‐dimensional filter (e.g., Király‐Proag et al., 2019). The number of control points defines the size of the subfaults and is selected on the basis of the magnitude of the EGF.…”
Section: Methodsmentioning
confidence: 99%
“…11). Király-Proag et al (2019) have recently analyzed the slip pattern of the main shock by back-projecting relative source time functions of the main events onto the reactivated fault plane. They found that most aftershocks that occurred within 5 d after the main shock are located at the edge of the M L 3.5 slip area, suggesting that stress concentration due to stress transfer may have played a major role.…”
Section: Effect Of the Gas On The Induced Seismicitymentioning
confidence: 99%
“…A striking example is the Enhanced Geothermal System (EGS) project in Basel, Switzerland, where seismicity was induced immediately below the city, which led to the suspension of the entire project (e.g., Giardini, 2009). Recent history clearly shows that the success of geo-energy, in particular geothermal projects, largely depends on the level at which we are able to control induced seismicity (Kraft et al, 2009;Kwiatek et al, 2019). There is an urgent need to communicate transparently with the public and employ methods that will safely keep the seismicity to a tolerable level (Giardini, 2009;Lee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Unsurprisingly, we find that the events within 55 m of the well (events 4364, 5695, 5386, and 7641) are much more sensitive to the location uncertainty and their rupture angles are less stable. However, the largest event, event 6389, occurred 132 m away and thus still unequivocally ruptured away from the well, not toward the well as found at other geothermal sites (e.g., Folesky et al., 2016; Kiraly‐Proag et al., 2019). We also examine the evolution of the rupture angle with respect to time and distance from the well (see Figure 6c), finding no clear trend.…”
Section: Combining Directivity and Focal Mechanismsmentioning
confidence: 87%